2016
DOI: 10.3389/fphar.2016.00499
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant, Anxiolytic, and Sedative Activities of Verbena officinalis

Abstract: We describe different neuropharmacological effects of Verbena officinalis crude extract (Vo.Cr). Pentylenetetrazole (PTZ)-induced seizures, elevated plus maze, light–dark box (LDB), open field and thiopental-induced sleeping test models were employed to evaluate Vo.Cr actions in mice. Vo.Cr dose-dependently (100–500 mg/Kg) delayed onset time of myoclonic jerks and tonic-clonic seizures, while decreased duration of tonic-clonic seizures (P < 0.05, P < 0.001 vs. saline group). Vo.Cr at 100 and 300–500 mg/Kg dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 37 publications
(38 reference statements)
2
48
0
1
Order By: Relevance
“…to PB1 treated mice. Each mouse was observed for onset times of myoclonic jerks, onset times and duration of tonic‐clonic seizures for 30 min (Khan, Khan, & Ahmed, ). Similar procedure was repeated with DPAA, but test compound was used at doses of 1, 2 and 5 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…to PB1 treated mice. Each mouse was observed for onset times of myoclonic jerks, onset times and duration of tonic‐clonic seizures for 30 min (Khan, Khan, & Ahmed, ). Similar procedure was repeated with DPAA, but test compound was used at doses of 1, 2 and 5 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Similar procedure was repeated with DPAA, but test compound was used at doses of 1, 2 and 5 mg/kg. Diazepam at dose of 1 mg/kg (Khan et al, ) and valproic acid at dose of 200 mg/kg (Raza, Khan, & Nadeem, ) were used as reference drug for PB1 and DPAA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The EPM and hole board method give consistent result for anxiolytic effect in this research work. Several study reported that the plants containing alkaloids, glycosides, phytosterols, flavonoids, saponins and tannins possess good anxiolytic activity [7,13,23]. The methanolic extract of T. recurva also contains alkaloids, glycosides, tannin (strongly), saponin and phytosterol.…”
Section: Discussionmentioning
confidence: 99%
“…The number of abdominal contraction was then counted at 5 min interval for 30 min. The percentage of analgesic activity was then calculated by using following formula [7]. Inhibition (%) = [Number of writhes (control) -number of writhes (test)]/Number of writhes (control) × 100…”
Section: Acetic Acid Induced Writhing Testmentioning
confidence: 99%
See 1 more Smart Citation